2013
DOI: 10.1371/journal.pone.0083756
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolomic Analysis of Omega-3 Fatty Acid-Mediated Attenuation of Western Diet-Induced Nonalcoholic Steatohepatitis in LDLR-/- Mice

Abstract: BackgroundNonalcoholic steatohepatitis (NASH) is a progressive form of nonalcoholic fatty liver disease and a risk factor for cirrhosis, hepatocellular carcinoma and liver failure. Previously, we reported that dietary docosahexaenoic acid (DHA, 22:6,n-3) was more effective than eicosapentaenoic acid (EPA, 20:5,n-3) at reversing western diet (WD) induced NASH in LDLR-/- mice.MethodsUsing livers from our previous study, we carried out a global non-targeted metabolomic approach to quantify diet-induced changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
97
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(101 citation statements)
references
References 45 publications
(88 reference statements)
4
97
0
Order By: Relevance
“…Although the WD + D diet signifi cantly lowered TLR2 agonists in plasma, WD + E and WD + D failed to lower plasma TLR4 agonists. Failure of the 3 PUFA-containing diets to suppress TLR4 agonist is consistent with our previous fi nding, which showed that dietary 3 PUFAs do not attenuate WD-induced endotoxinemia ( 18 ). Hepatic fi brosis is also linked to products derived from adipose tissue and cells involved in innate immunity, including adipokines and cytokines, respectively ( 52,53 ).…”
Section: Rna Extraction and Quantitative Rt-pcrsupporting
confidence: 89%
See 4 more Smart Citations
“…Although the WD + D diet signifi cantly lowered TLR2 agonists in plasma, WD + E and WD + D failed to lower plasma TLR4 agonists. Failure of the 3 PUFA-containing diets to suppress TLR4 agonist is consistent with our previous fi nding, which showed that dietary 3 PUFAs do not attenuate WD-induced endotoxinemia ( 18 ). Hepatic fi brosis is also linked to products derived from adipose tissue and cells involved in innate immunity, including adipokines and cytokines, respectively ( 52,53 ).…”
Section: Rna Extraction and Quantitative Rt-pcrsupporting
confidence: 89%
“…We also reported that adding EPA (20:5, 3) or DHA (22:6, 3) to the WD affected diet-induced hepatic fi brosis. DHA was more effective than EPA at attenuating WD-induced hepatic fi brosis ( 17,18,28 ). Although EPA and DHA attenuated WD-induced dyslipidemia, neither EPA nor DHA affected WD-induced body weight, the percent of body fat, blood glucose, or plasma endotoxin.…”
Section: Rna Extraction and Quantitative Rt-pcrmentioning
confidence: 84%
See 3 more Smart Citations